2005
DOI: 10.1186/1471-2180-5-55
|View full text |Cite
|
Sign up to set email alerts
|

In-house nucleic acid amplification tests for the detection of Mycobacterium tuberculosis in sputum specimens: meta-analysis and meta-regression

Abstract: Background: More than 200 studies related to nucleic acid amplification (NAA) tests to detect Mycobacterium tuberculosis directly from clinical specimens have appeared in the world literature since this technology was first introduced. NAA tests come as either commercial kits or as tests designed by the reporting investigators themselves (in-house tests). In-house tests vary widely in their accuracy, and factors that contribute to heterogeneity in test accuracy are not well characterized. Here, we used meta-an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
87
1
4

Year Published

2009
2009
2014
2014

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 158 publications
(95 citation statements)
references
References 59 publications
3
87
1
4
Order By: Relevance
“…Previously published reports demonstrated that the sensitivity of NAAT could be increased either by changing the target (9,11,12) or by modifying the DNA extraction protocol (13). Our multicenter study demonstrated similarly increased sensitivity by improving the sample preparation and RNA stabilization.…”
Section: Resultssupporting
confidence: 59%
See 4 more Smart Citations
“…Previously published reports demonstrated that the sensitivity of NAAT could be increased either by changing the target (9,11,12) or by modifying the DNA extraction protocol (13). Our multicenter study demonstrated similarly increased sensitivity by improving the sample preparation and RNA stabilization.…”
Section: Resultssupporting
confidence: 59%
“…By center, the sensitivities of TRC-2 were 90.5%, 80%, and 89.5% for Rome, Parma, and Paris, respectively. These sensitivities were in the range of recently published values for traditional commercialized PCR assays: 83 to 96.7% for the Cobas Amplicor assay (Roche Diagnostics) and 85.7 to 97.8% for the AMTD2 assay (bioMérieux-Gen-Probe) on respiratory specimens (2,11,18,19).…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations